2021
DOI: 10.1080/15538362.2021.1932693
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Pectin from Snot Apple (Azanza garckeana) Fruits with Potential Use in Zimbabwe

Abstract: Azanza garckeana (snot apple) is an underutilized indigenous fruit of southern Africa. The study was aimed at determining the functional characteristics and potential use of extracted pectin from A. garckeana (snot apple) fruits from Zimbabwe. A. garckeana (snot apple) fruits were collected from a semiarid communal area of Nhema, Zimbabwe. Pectin properties were determined using standard methods. Fruit jam was formulated with 53% (w/v) U. kirkiana fruit pulp, 45% (w/v) sugar, 1.5% (w/v) A. garckeana pectin, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…When the content increased, the pH value decreased significantly and the total acidity of the jam increased, indicating that Morus nigra L. provides a large amount of H + for the jam system. Low pH reduces the negative charge of pectin molecules and then promotes hydrogen bonding of pectin molecules leading to precipitation [29]. The addition of sucrose as a component in jam-making at low pH favors the gel formation of high-methoxy pectin [29,30].…”
Section: Physical and Chemical Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the content increased, the pH value decreased significantly and the total acidity of the jam increased, indicating that Morus nigra L. provides a large amount of H + for the jam system. Low pH reduces the negative charge of pectin molecules and then promotes hydrogen bonding of pectin molecules leading to precipitation [29]. The addition of sucrose as a component in jam-making at low pH favors the gel formation of high-methoxy pectin [29,30].…”
Section: Physical and Chemical Indicatorsmentioning
confidence: 99%
“…Low pH reduces the negative charge of pectin molecules and then promotes hydrogen bonding of pectin molecules leading to precipitation [29]. The addition of sucrose as a component in jam-making at low pH favors the gel formation of high-methoxy pectin [29,30]. However, the pH of jam should not be too low, as this can lead to the deterioration of organoleptic qualities such as glucose crystallization, granular texture, excessively acidic flavor, and oozing.…”
Section: Physical and Chemical Indicatorsmentioning
confidence: 99%
“…Its density varies due to its methoxyl content. 20 Due to increasing market demand, sources of pectin such as oranges, 21 bananas, 22 prickly pear, 23 snot apple, 24 sunflower head, 25 citrus sinensis, 26 pomegranate, 27 lemon, 28 and araca, 29 have been studied over the years. Pectins are extracted from lemon, orange peels, and apple pomace with conventional heating techniques (60-100 °C).…”
Section: Introductionmentioning
confidence: 99%
“…According to Branch, 1983 [2], the indigenous fruit-bearing tree species are rich in sugars, essential vitamins, and minerals. In context, a recent study showed that fruit could be used as a new source of pectin [14]. Multiple classes of phytochemical compounds such as ascorbic acid, amino acids, flavonoids, carotenoids, glucosides, phenols, lipids, and tannins have been isolated from A. garckeana [12].…”
Section: Introductionmentioning
confidence: 99%